Kingdom of Bahrain : Financial System Stability Assessment, including Reports on the Observance of Standards and Codes on the following topics, Banking Supervision, Insurance Supervision, Securities Regulation, and Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2006)
The Kingdom of Bahrain's Financial System Stability Assessment highlights banking supervision, insurance supervision, securities regulation, and antimoney laundering and combating the financing of terrorism. The banking sector is well capitalized. Asset quality has been improving and provisioning is high. Profitability surged in 2004-05, but historically, return on equity has been moderate for many institutions. Favorable liquidity conditions have caused regional equity and real estate markets to surge. Consumer lending has grown rapidly, although it slowed in 2005 following a tightening of loan to income limits.